I principi del pragmatismo pedagogico di Tsunesaburo Makiguchi - Spano, Andrea (Studi sulla Formazione/Open Journal of Education, 2024)
The pedagogical pragmatism of Makiguchi (1871-1944), a Japanese primary school teacher and first inspirer of the lay Buddhist association Soka Gakkai, was developed as opposition to the Japanese nationalism of the early twentieth century, that was characterized by the suppression of several freedoms (of thought and opinion, of religion and of education). In contrast to the imperial education model, Makiguchi proposed the philosophy of value creation, the foundation of his pedagogy. In this article we will discuss the thoughts of this author, focusing mainly on the Makiguchian declinations of the concepts of happiness, value and truth. These categories are the cornerstones of the educational project through which the master of the Soka movement hoped to inspire bottom-up social development.